2001
DOI: 10.1038/modpathol.3880474
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Analysis of HER-2/neu Immunoexpression among Various Histologic Subtypes and Grades of Osteosarcoma

Abstract: Overexpression of the HER-2/neu oncogene appears to have prognostic significance in breast cancer. Recently, some have reported a relationship between increased immunohistochemical expression in osteosarcoma and poor clinical outcome. Despite limited data, a pilot trial of Herceptin, which targets the oncogene product, has been initiated for the therapy of some metastatic osteosarcomas (CCG-P9852). Archival formalin-fixed, paraffin-embedded tissue obtained from 41 patients diagnosed with osteosarcoma was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
1
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 18 publications
3
44
1
3
Order By: Relevance
“…[17][18][19]23 In contrast, other studies observed Her-2/neu expression irrespective of histologic subtype and grade that was not associated with response to preoperative chemotherapy and clinical outcome. 22 Further reports did not observe Her-2/neu overexpression or even reported complete absence of Her-2/neu Figure 5 RNA was extracted from the indicated numbers of lasermicrodissected cells obtained from a decalcified, paraffinembedded and formalin-fixed osteosarcoma section and converted to cDNA. A measure of 1 ml of each cDNA was used to amplify Her-2/neu target sequence followed by a nested PCR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19]23 In contrast, other studies observed Her-2/neu expression irrespective of histologic subtype and grade that was not associated with response to preoperative chemotherapy and clinical outcome. 22 Further reports did not observe Her-2/neu overexpression or even reported complete absence of Her-2/neu Figure 5 RNA was extracted from the indicated numbers of lasermicrodissected cells obtained from a decalcified, paraffinembedded and formalin-fixed osteosarcoma section and converted to cDNA. A measure of 1 ml of each cDNA was used to amplify Her-2/neu target sequence followed by a nested PCR.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, observation of cytoplasmic positivity was independent of histologic subtype and grade and not associated with response to preoperative chemotherapy or disease progression. 21,22 On the other hand, a correlation of cytoplasmic Her-2/neu positivity with a shorter overall metastasis-free survival has recently been reported. 23 These discrepancies have extensively been discussed in the literature and attributed mainly to technical issues including the type of tissue, fixation method, storage conditions, sensitivity and reliability of the antibodies used, the scoring system and the interpretation of the results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of 12 metastatic samples, all 12 were HER2-positive. In bone tumors, several studies on HER2 have been performed for osteosarcoma and Ewing's sarcoma, the two most common types of neoplasms of the skeleton, but the findings reported thus far are contradictory (13)(14)(15)(16)(17). Particularly for osteosarcoma, the data reported are paradoxical, ranging from studies in which HER2-increased expression was detected in 63% of patients (14) to other studies in which it was uncommon or even absent (13,15,17).…”
Section: Metastatic Disease Number Of Patients ----------------------mentioning
confidence: 99%
“…In bone tumors, several studies on HER2 have been performed for osteosarcoma and Ewing's sarcoma, the two most common types of neoplasms of the skeleton, but the findings reported thus far are contradictory (13)(14)(15)(16)(17). Particularly for osteosarcoma, the data reported are paradoxical, ranging from studies in which HER2-increased expression was detected in 63% of patients (14) to other studies in which it was uncommon or even absent (13,15,17). Moreover, as extensively discussed by Anninga and colleagues (17), inconsistent findings have also been reported with regards to HER2 status and its prognostic significance.…”
Section: Metastatic Disease Number Of Patients ----------------------mentioning
confidence: 99%